The effectiveness of the Older prisoner Health and Social Care Assessment and Plan (OHSCAP): a randomised controlled trial - Katrina Forsyth; Laura Archer-Power; Jane Senior; Rachel Meacock; Roger Webb; Richard Emsley; Dawn Edge; Elizabeth Walsh; Stuart Ware; David Challis; Adrian Hayes; Kate O'Hara; et al. (National Institute for Health Research, 2017)
Background: Older people are the fastest-growing group in prisons in England and Wales and have complex health and social care needs that often remain unmet. Objectives: (1) Evaluate the efficacy of the Older prisoner Health and Social Care Assessment and Plan (OHSCAP) in improving (i) the ability to meet older male prisoners' health and social care needs, (ii) health-related quality of life (HRQoL), (iii) depressive symptoms and (iv) functional health and well-being and activities of daily living; (2) assess the quality of care plans produced; (3) explore the experiences of older prisoners receiving, and staff conducting, the OHSCAP; and (4) evaluate the cost-effectiveness of the OHSCAP compared with treatment as usual (TAU). Design: Multicentre, parallel-group randomised controlled trial (RCT) with follow-up at 3 months, with a nested qualitative study and quality audit of care plans (n = 150, 68%). Setting: Ten English prisons. Participants: Four hundred and ninety-seven newly arrived male prisoners aged ≥ 50 years with a discharge date at least 3 months from recruitment. A total of 14 prisoners and 11 staff participated in qualitative interviews. Intervention: Randomisation to OHSCAP or TAU. The OHSCAP group had health and social needs assessed by a trained health-care worker or prison officer. Care plans were devised and subsequent actions included professional support and appropriate referrals. Main outcome measures: Primary outcome measure - mean number of unmet health and social care needs as measured by the Camberwell Assessment of Need - Short Forensic Version. Secondary outcome measures - measures of functional health and well-being, depressive symptoms and HRQoL. A health economic evaluation was undertaken using service contact between baseline and follow-up and appropriate unit cost information. Results: A total of 497 prisoners were recruited (248 to OHSCAP and 249 to TAU). The 404 completed follow-ups were split evenly between the trial arms. No significant differences were observed between the intervention and TAU groups in relation to the primary outcome measure. The OHSCAP did not demonstrate convincing benefits in HRQoL over TAU, and there were no significant differences in relation to costs. Audit and qualitative data suggest that the intervention was not implemented as planned. Limitations: As a result of the limited follow-up period, potential long-term gains of the intervention were not measured. Some of the standardised tools had limited applicability in prison settings. Cost-effectiveness data were limited by unavailability of relevant unit cost data. Conclusions: The OHSCAP failed in its primary objective but, fundamentally, was not implemented as planned. This appears to have been attributable, in some part, to wider difficulties currently affecting the prison landscape, including reduced levels of staffing, the loss of specialist support roles for such initiatives and increased prevalence of regime disruption. Future work: Partnership working and information sharing across disciplines within prison settings require improvement. Research should explore the potential involvement of other prisoners and third-sector organisations in identifying and addressing older prisoners' health and social care needs to better match community provision. Further examination should be undertaken of how the prison regime and system affects the well-being of older prisoners. Future prison-based RCTs should carefully balance the fidelity of initiatives being evaluated and testing in a 'real-life' setting. Trial registration: Current Controlled Trials ISRCTN11841493. Funding: This project was funded by the National Institute for Health Research (NIHR) Health Services and Delivery Research programme and will be published in full in Health Services and Delivery Research; Vol. 5, No. 31. See the NIHR Journals Library website for further project information.